Effect of immobilization methods on service life of tyrosinase biosensors developed for dopamine monitoring - Sýs, Milan; Hartmanová, Aneta; Mikysek, Tomáš (BEST Servis, 2019)
An effect of immobilization methods on service life of tyrosinase amperometric biosensors was studied where dopamine was selected as a model analyte. Three different immobilization methods were tested such as incorporation of enzyme into the electrode material, immobilization using perfluorosulfonic acid polymer Nafion® and immobilization of enzyme by covalent bonding with the assistance of cross-linking agent glutaraldehyde. All prepared amperometric tyrosinase biosensors were stored dry in refrigerator at 5°C. Finally, the effect of used immobilization was discussed in details.
Vliv imobilizačních metod na životnost tyrosinázových biosenzorů vyvinutých pro monitorování dopaminu
Keywords: Amperometry; dopamine; immobilization methods; storage conditions; operational stability; tyrosinase; Amperometrie; dopamin; imobilizační metody; podmínky skladování; provozní stabilita; tyrosináza